Renal cortical involvement in children with first UTI: does it differ in the presence of primary VUR? - TUROĞLU, HALİL TURGUT; İNANIR, SABAHAT (SPRINGER, 2008)
The aim of this study was to investigate the influence of vesicoureteral reflux (VUR) on dimercaptosuccinic acid (DMSA) scintigraphic patterns in children with first symptomatic urinary tract infection (UTI). A total of 45 children with the diagnosis of first symptomatic UTI (28 girls, 17 boys, mean age 18 months, range 1 month-11 years) were reviewed. All DMSA scans were obtained within 2 months of bacteriologically proven UTI (median 21 days, mean 26 +/- 21, 14). After the exclusion of the patients with bilateral cortical lesions, 82 renal units were analyzed. The scintigraphic patterns included regional and global description of renal cortical abnormality (normal or decreased differential renal function, regional renal function (RRF), and the number and severity of cortical lesions). Vesicoureteral reflux was detected in 26 (32%) renal units (15 with grade 1-2, 11 with grade 3-4). Renal cortical abnormality was observed in 10 renal units without VUR (10/56, 17%) and 13 renal units with VUR (13/26: 50%). Of the 15 renal units, 5 with grade 1-2 VUR (5/15) and 8 of the 11 renal units with grade 3-4 VUR (8/11) had renal cortical involvement. The most common scintigraphic pattern in the patients without VUR was the preserved RRF (a parts per thousand yen45%) and two or fewer photon-deficient areas. On the other hand, a decreased RRF (< 45) associated with cortical lesions was the most frequent finding in patients with refluxing kidneys (8/26, 30%), especially in those with grade 3-4 disease. This investigation showed that the presence of VUR affects DMSA patterns in children with first symptomatic UTI.
Keywords: VCUG; DMSA; Reflux; Pyelonephritis; URINARY-TRACT-INFECTION; VESICOURETERAL REFLUX; SCINTIGRAPHY; PREDICTOR; DMSA